Leaf parameters responsible for imparting resistance to rice leaffolder, Cnaphalocrocis medinalis in landraces from North-East India - Sumalatha, J; Maheswari, T Uma; Padmavathi, Ch (Indian Journal of Plant Protection, 2020)
Rice (Oryza sativa L.) is one of the predominant food crops of the world and is the staple food for more than two billion people in the developing countries. Among the foliage feeding pests, leaf folder, Cnaphalocrocis medinalis is the most prevalent causing huge loss to the rice crop during both vegetative and reproductive stages. Leaf parameters like leaf length, leaf width and trichome density was measured in twenty three landraces screened against rice leaffolder during 2015 and 2016 kharif seasons. The leaf damaged area ranged between 81.6 and 286.9 mm2 in pooled analysis data of both the seasons. Out of 23 landraces, seven were identified as moderately resistant to rice leaffolder. Leaf length varied from 36.33 to 58.00 cm and leaf width ranged between 0.77 and 1.55 cm in both the seasons. Trichome density varied from 0.00 to 305.00 in different landraces. Pearson correlation co-efficients between leaffolder damage area and leaf parameters revealed a significant negative correlation with leaf length (r = - 0.7504) and a significant positive correlation with respect to leaf width (r = 0.8741). However, presence or absence of trichomes and their density did not show any relation with respect to leaffolder damage.